Pleural fluid smear AFB positivity: To search for underlying immunosuppression - Santra, Avradip; Nandi, Saumen; Kundu, Soumya; Sen, Arya (Bangladesh Journal of Medical Science, 2016)
Tubercular pleural effusion may cause a diagnostic dilemma as mycobacterium could not be detected in most cases due to paucibacillary nature of effusion. Pleural fluid AFB smear is positive in less than ten percent cases except in patients with tubercular empyema. However, percentage of AFB positivity in smear increases significantly if there is underlying immunodeficiency disorder. We hereby report a case of unilateral pleural effusion which was diagnosed to be of tubercular origin based on biochemical and cytological parameters along with plenty of AFB in pleural fluid smear. The patient was subsequently evaluated for any associated immunosuppression and he was found to have non-Hodgkin lymphoma. Bangladesh Journal of Medical Science Vol.15(2) 2016 p.286-288